2019
DOI: 10.1097/sap.0000000000002015
|View full text |Cite
|
Sign up to set email alerts
|

Scope of Hand Surgery Using Surgeon Administered Local/Regional Anaesthesia

Abstract: Introduction Hand and wrist surgeries are often carried out under local/regional anesthesia. We describe our experience using Surgeon Administered Local/Regional Anaesthesia (SALoRA) without sedation to deliver acute and elective hand surgery anesthesia in a tertiary public hospital in Singapore. This is in comparison to wide awake local anesthesia no tourniquet, which has been increasing in popularity. Methods Retrospective analysis was conducted on al… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
1

Relationship

5
1

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 25 publications
0
8
0
Order By: Relevance
“…Our operative case mix was significantly affected, with a shift from 61% elective and 39% emergency surgeries 24 in the prepandemic period, to 46.5% elective and 53.5% for emergency surgeries during the pandemic period. There was no significant change in outpatient flow despite the postponement of all elective consultation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our operative case mix was significantly affected, with a shift from 61% elective and 39% emergency surgeries 24 in the prepandemic period, to 46.5% elective and 53.5% for emergency surgeries during the pandemic period. There was no significant change in outpatient flow despite the postponement of all elective consultation.…”
Section: Discussionmentioning
confidence: 99%
“…Since the first reported COVID-19 on 31 December 2019, by China, 1 the disease has spread both locally and outside China, first in Asia and then globally. WHO on the 12 March 2020 declared COVID-19 as a pandemic noted 125 048 confirmed cases globally with 6729 new cases in the preceding 24 As China's cases continue to stabilise, globally the number of new cases continued to grow. China's control measures included the lockdown in Hubei province, which restricted household transmission leading to the burn-out of the virus.…”
Section: Introductionmentioning
confidence: 99%
“…A quantitative analysis of the commonly performed procedures was conducted from a previous study [40]. The expert panel used this to determine the index procedure (micro suturing) for this research and the motor skills with various tasks and subtasks required to perform micro suturing [40]. For this study, the procedure of nerve grafts and repair was chosen by the expert panel as the index procedure.…”
Section: Analysis Of Key Tasksmentioning
confidence: 99%
“…[2][3][4][5][6] In addition, improved cost and time effectiveness further supports this transition at an institutional level. 2,4,7,8 Although use and familiarity of RLA is increasing, acceptance from patients and health care professionals ultimately determine the success of RLA. There have been few studies that have examined patient-and surgeon-reported experiences in RLA in upper limb surgeries, with few using a validated questionnaire to specifically assess the level of satisfaction of patients undergoing RLA.…”
Section: Introductionmentioning
confidence: 99%
“…2 3 4 5 6 In addition, improved cost and time effectiveness further supports this transition at an institutional level. 2 4 7 8…”
Section: Introductionmentioning
confidence: 99%